(untitled) (Journal of Oriental Studies, 2019)
This paper highlights some of the difficulties that translators face in their attempts to render a culturebound terms as accurately as possible from its source text. The task is very complex, and the limits of such work are certainly a challenge as a translator tries to be faithful to the source text, to handle crosscultural concepts, and to construct a correct version in the target language. Although target texts can only be an approximate version of the source text, and although there are insurmountable restrictions on literary translation, the latter continues to enrich the universal culture of peace. Some translators believe that the reader should be involved in the process of learning, should cooperate with the translation and be creative. He / she is able to think out the meaning himself and get acquainted with a new culture, to catch its “original color” or “taste”. The purpose of the translator is to promote a better understanding of the cultural heritage. He / she seeks to guide and stimulate readers to discover another world, so that they can interpret and, in their own way, appreciate the differences. Materials of the article can be useful to every researcher who deals with issues of translation and accurate transmission of cultural terms. Key words: Approximate translation, culturebound terms, source text, target text, accuracy.